The role of PPAT in giving legal condition to the issuance of land and building assets in a limited company - Kevin Jonathan (Technium Social Sciences Journal, 2021)
This type of research usid in this research is normative legal research. Notary status, that in making each deed must be clear, correct, complete, and in accordance with Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position (Law No.2-2014). In making the deed of establishment of the foundation and it’s amendments, the notary must also be responsible for the deed he makes because there must be sanctions that will be imposed if the deed isn’t in accordance with the applicable regulations, however in practice, there are also Notaries whose deeds aren’t in accordance with Law No. 2-2014 and also the Notary Code of Ethics (KEN) without feeling afraid of the sanctions it will receive because it causes one of the parties to feel aggrieved. The Deed of Sale and Purchase of Land and Building is the most importanat factor in the assets of a Limited Liability Company. The role of PPAT in providing legal certainty to issue AJB for Land and Buildings must go through various approaches, including applying the principle of prudence to carry out its duties as per the PPAT Position regulations.